The physical corner of the crime of recruiting children in armed conflict - ابراهيم صباح سامي; جاسم اسراء عبد الصاحب (Journal of Legal Sciences, 2019)
Children are considered the most affected group in armed conflicts because of the diversity and diversity of the forms of aggression against them.Their recruitment into armed conflicts is one of the most dangerous images. Therefore, the use of children in armed conflicts, it is not a modern phenomenon that is confined to contemporary armed conflicts, but has been used in ancient wars and different times and civilizations. However, this phenomenon has taken on new dimensions in contemporary conflicts, the warring parties are now considered to be essential in their ranks as groups that are easy to use and recruit in armed conflicts. They are no longer limited to helping roles but are playing a key role in carrying arms and fighting in the front lines of these conflicts. Which is a clear and explicit violation of all international, domestic and ethical criminal norms that encourage respect for, protection and protection of the rights of children.